2019
DOI: 10.1002/jcp.28564
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the STAT3/microRNA‐21 pathway participates in angiotensin II‐induced angiogenesis

Abstract: Angiotensin II (AngII) facilitates angiogenesis that is associated with the continuous progression of atherosclerotic plaques, but the underlying mechanisms are still not fully understood. Several microRNAs (miRNAs) have been shown to promote angiogenesis; however, whether miRNAs play a crucial role in AngII‐induced angiogenesis remains unclear. This study evaluated the functional involvement of miRNA‐21 (miR‐21) in the AngII‐mediated proangiogenic response in human microvascular endothelial cells (HMECs). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 52 publications
(68 reference statements)
3
14
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) is crucial in compensated angiogenesis associated with maintaining cardiac function ( [61]). AngII and LIPUS irradiation have been reported to induce endothelium-derived angiogenesis by different mechanisms ( [18,62]), which was in agreement with our results that increased protein expression of VEGF was found in mice hearts after AngII and/or LIPUS treatment. Given that caveolin-1 is highly expressed in the endothelium ( [63]), the above reasons may explain the increased caveolin-1 expression in heart tissues in the model group.…”
Section: Discussionsupporting
confidence: 93%
“…Vascular endothelial growth factor (VEGF) is crucial in compensated angiogenesis associated with maintaining cardiac function ( [61]). AngII and LIPUS irradiation have been reported to induce endothelium-derived angiogenesis by different mechanisms ( [18,62]), which was in agreement with our results that increased protein expression of VEGF was found in mice hearts after AngII and/or LIPUS treatment. Given that caveolin-1 is highly expressed in the endothelium ( [63]), the above reasons may explain the increased caveolin-1 expression in heart tissues in the model group.…”
Section: Discussionsupporting
confidence: 93%
“…UA-Exos influence the circRNA-0006896-miR-1264-DNMT1 axis in HUVECs. A previous study reported that HUVEC proliferation and migration are important events that induce plaque destabilization (23,24). The signaling molecules carried by exosomes may affect the biological behavior of target cells in the microenvironment (25).…”
Section: Rt-qpcr Validation Prediction Of Mrna-mirna-circrna Relatiomentioning
confidence: 99%
“…Mechanistically, p-STAT3 binds to the promoter region of miR-199a-2 for regulation (Zhou et al, 2019). Three functional binding sites of STAT3 in the Mir21 promoter region mediate angiogenesis (Chen et al, 2019). During Th17 polarization, IL-6-activated STAT3 has particularly important roles in the expression of Rorγt, a Th17 lineage marker.…”
Section: Discussionmentioning
confidence: 99%